ESTUDO DA PROLIFERAÇÃO CELULAR ATRAVÉS DOS MARCADORES KI-67 E CD71 NAS LEUCEMIAS AGUDAS EM CENTRO ONCOLÓGICO DE REFERÊNCIA NO ESTADO DO MARANHÃO. - Marinho, Heliana Trindade (2010)
This research aimed to study cell proliferation by Ki-67 marker and CD71 in acute leukemias, as well as establish the relationship between them and their relationship to therapeutic response. Patients were selected prospectively commencing in December 2008 and ending in November 2009 (12 months). Samples were collected from bone marrow or peripheral blood of 54 patients diagnosed with acute leukemia, from the referral hospital for cancer treatment in the state of Maranhão (northeastern Brazil) and determined the expression of Ki-67 markers and CD71 by flow cytometry. Most patients were from the northeast, followed by the central, northwest, southwest and southeast of Maranhão. No patients were in southern state. The values of Ki-67 in bone marrow and peripheral blood in the patients were higher in B-ALL than other acute leukemias. The bone marrow CD71 showed increased expression in T-ALL and peripheral blood, increased expression in AML. Was no statistical difference in Ki-67 in peripheral blood and bone marrow only in AML. A significant positive correlation between Ki-67 and CD71 in peripheral blood in B-ALL. In bone marrow, the markers showed a linear correlation in AML. No relationship was found between markers of cell proliferation and response to treatment. A continuing study of cell proliferation with a greater number of patients, coupled with other techniques of cell proliferation it is necessary to evaluate other